Lateglacial to Late Holocene palaeoclimatic and palaeoenvironmental reconstruction of El Mirador cave (Sierra de Atapuerca, Burgos, Spain) using the small-mammal assemblages - Bañuls-Cardona, Sandra (2017)
El Mirador is a cave in the Sierra de Atapuerca (northern Iberian Peninsula) that contains 27 archaeological layers from the Lateglacial to the LateHolocene. A total of 4436 small-mammal remains have been analysed from these layers, and 19 taxa have been identified (three insectivores, seven chiropters and nine rodents). The palaeoenvironmental reconstruction based on a small-mammal analysis suggests that the entire sequence is dominated by a woodland landscape. Our climatic analysis characterises the climate in terms of an evolution from a cool and arid period in the Pleistocene layers (16,000 to 14,000 cal yr BP), probably related to Heinrich Event 1, to humid conditions and temperatures similar to nowadays in the Holocene layers in general. In MIR23 andMIR22 (7300 to 6800 cal yr BP) we detect an increase in temperature to levels above current values and an important decrease in rainfall. These climatic characteristics could be related to the end of the African Humid Period.Moreover, a short, slightly cooler event is registered inMIR11 (ca. 6300 to 5900 cal yr BP), coinciding with a change in the economic pattern in ElMirador. The results obtained on the basis of small-mammal studies are compared withmultiproxy terrestrial data (pollen, charcoal, phytoliths, geochemistry, large mammals) and the Greenland ice-core record, aswell as various other core records closer to the coasts of the Iberian Peninsula (MD95-2042,MD99-2331,MD95-2043 andSMP02-3). These comparisons showthe agreement of the palaeoenvironmental and palaeoclimatic resultswith all the previousmultiproxy and core-record data.